Temporal Trends in Inadequate Vegetable and Fruit Consumption Among Adolescents Aged 12–15 Years From 31 Countries in Asia, Africa, and the Americas - Lee Smith; Guillermo F. López Sánchez; Mark A. Tully; Yvonne Barnett; Laurie Butler; Helen Keyes; Louis Jacob; Karel Kostev; Hans Oh; Masoud Rahmati; Jae Il Shin; Ai Koyanagi (Health Science Reports)
ABSTRACT Background and Aims A low intake of fruit and vegetable consumption has been found to be associated with a plethora of negative health outcomes in adolescents. However, there is a scarcity of literature on long‐term trends in fruit and vegetable intake in the adolescent population. Therefore, we examined this trend in a nationally representative sample of adolescents (12–15 years) attending school in 31 countries, including Africa, Asia, and the Americas, where investigation of such trends has been scarce. Methods The present study analyzed data from the Global School‐based Student Health Survey 2003–2017. The prevalence (95% CI) of inadequate fruit and vegetable intake (i.e., consumption < 5 times/day) was calculated for each survey, and crude linear trends were examined by linear regression models for each country. Results We analyzed data from students (n = 193,388) aged 12–15 years [mean (SD) age 13.7 (1.0) years; 49.0% boys]. A high overall prevalence of inadequate fruit and vegetable consumption was found (75%). We observed increasing, decreasing, and stable trends in 6, 3, and 22 countries, respectively. In countries where decreasing trends were found, this decrease was minimal. Moreover, the majority of countries with stable trends exhibited a high prevalence of inadequate fruit and vegetable intake across multiple years. Conclusion Our data show that inadequate fruit and vegetable consumption among adolescents is a major global problem with almost no improvements being observed in recent years. Intensification of global efforts to combat inadequate fruit and vegetable consumption is necessary.